2015
DOI: 10.1002/14651858.cd011735
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitors for fibromyalgia syndrome

Abstract: Background Fibromyalgia is a clinically well-defined chronic condition with a biopsychosocial aetiology. Fibromyalgia is characterized by chronic widespread musculoskeletal pain, sleep problems, cognitive dysfunction, and fatigue. Patients often report high disability levels and poor quality of life. Since there is no specific treatment that alters the pathogenesis of fibromyalgia, drug therapy focuses on pain reduction and improvement of other aversive symptoms. Objectives The objective was to assess the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 63 publications
0
26
0
4
Order By: Relevance
“…Rather than analyzing the quality of evidence of clinical trials using these substances, we were interested in assigning the active principle and IUPAC names to the reported compounds, to facilitate our downstream analysis (Table 3). Additional literature supporting the use of compounds for each of the six classes described by Häuser et al, to treat FM patients is provided in Table 3 [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93].…”
Section: Polypharmacy In Fmmentioning
confidence: 99%
See 1 more Smart Citation
“…Rather than analyzing the quality of evidence of clinical trials using these substances, we were interested in assigning the active principle and IUPAC names to the reported compounds, to facilitate our downstream analysis (Table 3). Additional literature supporting the use of compounds for each of the six classes described by Häuser et al, to treat FM patients is provided in Table 3 [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93].…”
Section: Polypharmacy In Fmmentioning
confidence: 99%
“…Collatz A et al, 2016 [97] Proliferation inductor from B cells Although possibly not complete, Tables 3 and 4 include the most representative compounds to treat FM and ME/CFS according to the consulted authors [44,48,[76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92][93][99][100][101][102][103][104][105][106][107]. Unexpectedly, a single IUPAC overlap, corresponding to the Selective Serotonin Reuptake Inhibitor (SSRI) Fluoxetine, was found for drugs commonly prescribed for FM and ME/CFS (in bold in Tables 3 &4); indicating little prescription overlap at the IUPAC name level despite both groups of patients presenting common symptomatology.…”
Section: Othersmentioning
confidence: 99%
“…A recent Cochrane review concluded that there was no unbiased evidence with regards to superiority of SSRIs to placebo in treating the key symptoms of fibromyalgia (pain, fatigue and sleep problems), however they might be considered for treating depression in this group of patients [28]. National and international guidelines are mixed with regards to their recommendations on SSRIs.…”
Section: Selective Serotonin Reuptake Inhibitorsmentioning
confidence: 99%
“…Klinik pratikte fibromiyalji tedavisinde çok sık kullanılan selektif serotonin geri alım inhibitörleri (sitolopram, fuloksetin, esitalopram, floksamin, paroksetin, sertralin) plaseboya kıyasla hastalığın major semptomları olan ağrı, yorgunluk ve uyku problemleri üzerine daha etkili olduğuna dair hala yeterli kanıt yoktur. Bununla birlikte bu ilaçlar fibromiyaljiye eşlik eden depresyon tedavisinde çok etkilidirler 37 .…”
Section: Selektif Serotonin Gerialım Inhibitörleriunclassified